A Fuzzy Semantic for BDI Logic. Issue 2 (3rd April 2021) - Cruz, Anderson; dos Santos, André V.; Santiago, Regivan H. N.; Bedregal, Benjamin
Abstract : The BDI logic is an important and widely used theoretical apparatus to represent and reason about rational agents. However, the BDI logics are incomplete regarding the intention reconsideration, override of intention, the deliberation process, and belief revision. These are essential processes of the BDI model. Also, some rational agents, especially human being, have not the approximate reasoning well represented by the BDI logics. So, in this paper, we define fuzzy semantics for a BDI language that is capable to eliminate those limitations. Additionally, we show how this paper is related to current works about BDI agents and discuss how those limitations can be fixed through the extension of the BDI logic to a fuzzy BDI logic.